1994
DOI: 10.1002/ar.1092390407
|View full text |Cite
|
Sign up to set email alerts
|

Differences in osteonal micromorphology between tensile and compressive cortices of a bending skeletal system: Indications of potential strain‐specific differences in bone microstructure

Abstract: These osteonal microstructure and cortical porosity differences may be adaptations related to regional differences in strain mode and/or strain magnitude. This may be related to the disparity in mechanical properties of compact bone in tension vs. compression. These differences may reflect a capacity of bone to process local and regional strain-related information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 70 publications
6
110
0
Order By: Relevance
“…tension versus compression) and the corresponding disparity in strain magnitude (greater in the compressed cortex) may evoke regional strain-related adaptive responses. For example, compressed regions tend to have greater osteon population density and/or more oblique-to-transverse collagen fiber orientation than opposing tension cortices (Marotti, 1963;Lanyon and Bourn, 1979;Bouvier and Hylander, 1981;Portigliatti Barbos et al, 1984;Martin and Burr, 1989;Mason et al, 1995;Skedros et al, 1994Skedros et al, , 1996Skedros et al, , 1997Skedros et al, , 2001bTakano et al, 1999;Kalmey and Lovejoy, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…tension versus compression) and the corresponding disparity in strain magnitude (greater in the compressed cortex) may evoke regional strain-related adaptive responses. For example, compressed regions tend to have greater osteon population density and/or more oblique-to-transverse collagen fiber orientation than opposing tension cortices (Marotti, 1963;Lanyon and Bourn, 1979;Bouvier and Hylander, 1981;Portigliatti Barbos et al, 1984;Martin and Burr, 1989;Mason et al, 1995;Skedros et al, 1994Skedros et al, , 1996Skedros et al, , 1997Skedros et al, , 2001bTakano et al, 1999;Kalmey and Lovejoy, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Independent work done by Su et al (1999), Lai et al (2005), Skedros et al, (1994), Abdel-Wahab et al (2010) and Li et al (2012a and b) confirmed a correlation between mechanical properties and local anatomic position for both artiodactyl and human bone. The reasons for this correlation defined as the effect of mineral content (Lai et al, 2005;Skedros et al, 1997); adaptive transition of microstructure (Riggs et al, 1993a); prevalence of specific strain or local motion (Su et al, 1999).…”
Section: Introductionmentioning
confidence: 88%
“…Also, the fractional area of secondary bone was found to be greater in the areas of the cortex that receive more deleterious loading conditions. (Skedros et al, 1994(Skedros et al, , 2001). In the calcanei, significantly smaller osteons were found in the highly strained part of cortex (Skedros et al, 2001), a result also obtained theoretically using a mechano-biological model of bone remodeling (van Oers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%